Alterations in T and B Cell Receptor Repertoires Patterns in Patients With IL10 Signaling Defects and History of Infantile-Onset IBD - Werner, Lael; Lee, Yu Nee; Rechavi, Erez; Lev, Atar; Yerushalmi, Baruch; Ling, Galina; Shah, Neil; Uhlig, Holm H.; Weiss, Batia; Somech, Raz; Snapper, Scott B.; Shouval, Dror S. (Frontiers in Immunology, 2020)
Patients with loss-of-function mutations in IL10 or IL10 receptor (IL10R) genes develop severe, medical-refractory, infantile-onset inflammatory bowel disease (IBD). We have previously reported significant alterations in innate and adaptive immune responses in these patients. Next generation sequencing platforms enable a comprehensive assessment of T cell receptor (TCR) and B cell receptor (BCR) repertoire patterns. We aimed to characterize TCR and BCR features in peripheral blood of patients with deleterious IL10 signaling defects. DNA was isolated from blood of seven patients with IL10R mutations and one with an IL10 mutation, along with eight controls, and subjected to next generation sequencing of TRB and IgH loci. A significant increase in clonality was observed in both TCR and BCR repertoires in circulating lymphocytes of IL10/IL10R-deficient patients, but to a much greater extent in T cells. Furthermore, short CDR3β length and altered hydrophobicity were demonstrated in T cells of patients, but not in B cells, secondary to lower rates of insertions of nucleotides, but not deletions, at the V-, D-, or J-junctions. We were unable to observe specific T or B clones that were limited only to the patients or among controls. Moreover, the expanded T cells clones were unique to each patient. In conclusion, next generation sequencing of the TCR and BCR is a powerful tool for characterizing the adaptive immune cell phenotype and function in immune-mediated disorders. The oligoclonality observed among IL10/IL10R-deficient patients may suggest specialization of unique clones that likely have a role in mediating tissue damage. Nevertheless, the lack of shared clones between patients provides another piece of evidence that the adaptive immune response in IBD is not triggered against common antigens. Additional studies are required to define the specific antigens that interact with the expanded IL10/IL10R-deficient clones.